View of the Shikhara of the Sarvatobhadra - Temples of India Project Team (Jio Institute, 2024)
A closer view of the shikhara (superstructure) of the sarvatobhadra (open from all sides) reveals it's stylized like a phamsana (pyramidal) shikhara. It consists of three mouldings that decrease in size, with a gavaksha (false window) on the frontal side of these mouldings. The mouldings are capped by a disc at the centre. The shikhara gives the sarvatobhadra the appearance of a miniature shrine.